2018
DOI: 10.21475/ajcs.18.12.05.pne667
|View full text |Cite
|
Sign up to set email alerts
|

Oil, protein and fatty acid profiles of Brazilian soybean cultivars in multi-environmental trials

Abstract: Soybean is an important oil and protein source for human and animal food, as well as being used in the production of biofuel. Brazilian soybean is known for its quality, especially with regard to its high protein content. This work aimed to present a screening of Brazilian soybean cropped at different locations, to assess the composition of seed with regard to the protein, oil and fatty acid contents. We screened 46 cultivars, which represent more than 50% of the soybean cultivars produced in the South-Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…The genotypes that had higher values for protein content, showed statistically lower oil content. These results support the idea that oil and protein contents have a negative association (Gesteira et al 2018, Jiang et al 2018, Matei et al 2018. The oil and protein content is presented in Table 5.…”
Section: Resultssupporting
confidence: 85%
“…The genotypes that had higher values for protein content, showed statistically lower oil content. These results support the idea that oil and protein contents have a negative association (Gesteira et al 2018, Jiang et al 2018, Matei et al 2018. The oil and protein content is presented in Table 5.…”
Section: Resultssupporting
confidence: 85%
“…Numerous authors use different yieldstability statistics to evaluate performance of tested genotypes (YAN and RAJCAN, 2003), e.g. GGE biplot (ZHANG et al, 2005;MATEI et al, 2018), Wricke's ecovalence (SILVA et al, 2016), regression (b), determination (R 2 ) and deviation of the linear regression (σ 2 ) coefficients (LIMA et al, 2000), regression coefficient (b) (YAN et al, 2010), coefficients of variation (CV) (POPOVIĆ et al, 2012), amongst others. Interestingly, however, all stability indices are relative to each study and determine the best genotype among tested cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Higher values of GY, OIL, PRT, PH, and TGW are desirable for soybean crop (Matei et al., ; Matei et al., ). Medium‐cycle cultivars have been prioritized because they present higher productive potential and are preferred by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Leite et al (2018) indicated that exploratory multivariate techniques can be applied to select genotypes by analyzing the agronomic traits altogether, increasing the chance of success of a breeding program. Higher values of GY, OIL, PRT, PH, and TGW are desirable for soybean crop (Matei et al, 2017;Matei et al, 2018). Medium-cycle cultivars have been prioritized because they present higher productive potential and are preferred by farmers.…”
Section: Discussionmentioning
confidence: 99%